2018
DOI: 10.1007/s00520-018-4102-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among symptom clusters, quality of life, and treatment-specific optimism in patients with cancer

Abstract: PurposeThere is increasing evidence that disease and therapy-related symptoms frequently co-occur in so-called symptom clusters (SCs), which may significantly impair quality of life in patients with cancer. Although psychosocial resources may play pivotal roles in maintaining or improving quality of life, they have been neglected in SC research. Therefore, we aim to identify SCs and their relative impact on quality of life when psychosocial resources are accounted for.MethodsPatients with cancer (n = 304) unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 45 publications
3
33
0
1
Order By: Relevance
“…One of the performance indicators of unpleasant symptoms is quality of life (QoL). In addition, empirical studies also show that critical patient‐reported symptoms depend not only on objective demographic characteristics and disease‐related information, but also on several psychosocial resources that have been consistently linked with patient outcomes (Matzka, Köck‐Hódi, Jahn, & Mayer, ; Wu, Tsai, et al, ; Wu, Qin, et al, ). As an important component of positive psychology, resilience is a dynamic psychosocial resource of adapting well in the face of adversity or stress.…”
Section: Introductionmentioning
confidence: 99%
“…One of the performance indicators of unpleasant symptoms is quality of life (QoL). In addition, empirical studies also show that critical patient‐reported symptoms depend not only on objective demographic characteristics and disease‐related information, but also on several psychosocial resources that have been consistently linked with patient outcomes (Matzka, Köck‐Hódi, Jahn, & Mayer, ; Wu, Tsai, et al, ; Wu, Qin, et al, ). As an important component of positive psychology, resilience is a dynamic psychosocial resource of adapting well in the face of adversity or stress.…”
Section: Introductionmentioning
confidence: 99%
“…It integrates the complex physiological and psychosocial aspects of a person’s whole life (Moy et al, 2009). Symptom clusters that significantly impact HRQoL in cancer patients have been identified in numerous cancer studies (Hwang, Cho, & Yoo, 2016; Matzka, Kock-Hodi, Jahn, & Mayer, 2018; Rha & Lee, 2017), which have advanced interventions aimed to promote disease management and HRQoL(Golan-Vered & Pud, 2013; Yennurajalingam, Williams, Chisholm, & Bruera, 2016). It is widely recognized that HRQoL is impaired in patients with COPD (Wacker et al, 2016).…”
mentioning
confidence: 99%
“…No permission is needed for its use, and it was completed by the researchers. These tools were used in this study because they are the most used data measurement tool in symptom cluster research (Al Qadire & Al Khalaileh, 2016;Matzka et al, 2018;Skerman et al, 2012;Yesilbalkan et al, 2020), there are available and valid in Arabic, and they are easy and free to use for research purposes.…”
Section: Karnofsky Performance Status Scalementioning
confidence: 99%